2020
DOI: 10.1098/rspa.2020.0376
|View full text |Cite
|
Sign up to set email alerts
|

A modelling framework to assess the likely effectiveness of facemasks in combination with ‘lock-down’ in managing the COVID-19 pandemic

Abstract: COVID-19 is characterized by an infectious pre-symptomatic period, when newly infected individuals can unwittingly infect others. We are interested in what benefits facemasks could offer as a non-pharmaceutical intervention, especially in the settings where high-technology interventions, such as contact tracing using mobile apps or rapid case detection via molecular tests, are not sustainable. Here, we report the results of two mathematical models and show that facemask use by the public could make a major con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
270
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(289 citation statements)
references
References 62 publications
12
270
0
7
Order By: Relevance
“…19 Another recent study described the e cacy of medical mask-wearing by asymptomatic individuals as well as lockdown at the population level. 20 We observed that the participants in Japan were signi cantly less likely to engage in any of the avoidance behaviors examined compared to those in Spain and the UK. These results were are similar to those of the other surveys conducted concurrently.…”
Section: Discussionmentioning
confidence: 61%
“…19 Another recent study described the e cacy of medical mask-wearing by asymptomatic individuals as well as lockdown at the population level. 20 We observed that the participants in Japan were signi cantly less likely to engage in any of the avoidance behaviors examined compared to those in Spain and the UK. These results were are similar to those of the other surveys conducted concurrently.…”
Section: Discussionmentioning
confidence: 61%
“…The effects of the fractional orders are distinctive; the solution curves for 0 < α < 1 show delay in the epidemic peak and flatten faster, see Figure 5 (a), (c) and (d). These observations are known to occur in epidemic models with intervention [67]. The impacts of α is even more pronounced for smaller orders; for example, compare α = 0.9 and α = 0.6 in Figure 5 (c).…”
Section: Numerical Results and Analysismentioning
confidence: 75%
“…From the results of the present study, it is clear that, in addition to structural factors related to material living conditions and the mechanisms of discrimination in access to healthcare resources, even with the lack of government actions or ambiguity with respect to those actions, behavioral factors can affect compliance with social distancing measures, as shown by the reduction in social mobility in Nicaragua or even in Brazil or Mexico. Another aspect that merits investigation is the contribution of the widespread use of facemasks in the epidemic in Latin America, which, alone or in combination with lockdown, has been indicated as having great potential to reduce the transmission of COVID-19 [67,68].…”
Section: Discussionmentioning
confidence: 99%